2009
DOI: 10.1002/dev.20409
|View full text |Cite
|
Sign up to set email alerts
|

Development of behavior in the litter huddle in rat pups: Within‐ and between‐litter differences

Abstract: Early postnatal growth in mammals can be considerably influenced by litter size and often differs among littermates in relation to birth mass. In a study of Long Evans laboratory rats we asked whether within- and between-litter differences in body mass and growth are related to behavioral development during early postnatal life. For this, we analyzed the amount of general motor activity and the display of directed, seemingly goal-oriented interactions within the litter huddle in previsual pups. During the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
(56 reference statements)
3
37
0
Order By: Relevance
“…They also occupy more central, thermally advantageous positions in the litter huddle while expending significantly less time in presumably energetically costly efforts to gain these by climbing over or pushing between littermates than their lighter sibs, a pattern we have also found in newborn rats ( Fig. 4; Bautista, García-Torres, et al, 2008;Bautista, García-Torres, Prager, Hudson, & Rödel, 2010).…”
Section: Physiology and Behaviormentioning
confidence: 69%
See 1 more Smart Citation
“…They also occupy more central, thermally advantageous positions in the litter huddle while expending significantly less time in presumably energetically costly efforts to gain these by climbing over or pushing between littermates than their lighter sibs, a pattern we have also found in newborn rats ( Fig. 4; Bautista, García-Torres, et al, 2008;Bautista, García-Torres, Prager, Hudson, & Rödel, 2010).…”
Section: Physiology and Behaviormentioning
confidence: 69%
“…In conditions of sustained cold, as can be the case for low-bodymass young occupying the periphery of the huddle, BAT stores can be rapidly depleted, resulting in a life-threatening situation in which the cool, moribund young can no longer successfully compete in the brief daily scramble for nipples (Fig. 5;Bautista et al, 2003; (2008) and Bautista et al (2010). Gilbert et al, 2007; cf.…”
Section: Physiology and Behaviormentioning
confidence: 97%
“…Prior studies have shown that neonate weight is related to neonate huddling (Bautista, García-Torres, Prager, Hudson, & Rödel, 2010) and may predict maternal licking rates (Cavigelli et al, 2010). Litter and sex effects were controlled by centering variables to the family mean for same-sex siblings.…”
Section: Developmental Psychobiologymentioning
confidence: 99%
“…In mammals, for example, the number of litter siblings can vary considerably, as it is the case in many rodents and lagomorphs, and has been shown to influence the early physiological and physical development (reviewed in Hudson & Trillmich, 2008;Hudson et al, 2011;Mock & Parker, 1997). Most importantly, animals born to larger litters usually show a lower body mass development until weaning and beyond (Bautista, Garcia-Torres, Prager, Hudson, & Rödel, 2010;Mendl, 1988;Rödel, Prager, Stefanski, von Holst, & Hudson, 2008). But also other physiological parameters, such as the development of HPA axis functionality are reported to be slower in young from larger litters (Rödel, Meyer, Prager, Stefanski, & Hudson, 2010).…”
Section: Introductionmentioning
confidence: 96%